Analyzing the contemporary Palestinian revolutionary folk song “Fida'i” by the palestinian poet in the lense of literary criticism method: Sa’eed Al-Muzayyen as model - Rahmah Ahmad H. Osman,; Nur Farhana Mohamad Zainol, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Palestinian folk song is a medium used by Palestinians to express the reality happened in the land of Palestine, especially after the Zionist occupied their land and stole their belongings, houses, dreams and hopes, and since the occupation began, Palestinian folk song had become a form of resistance – even though is was not called as a revolutionary song –. Hence this research attempt to study one of the contemporary Palestinian revolutionary folk songs, which is "Fida’i" written by the Palestinian poet Sa’eed al-Muzayyen, by using the literary criticism approach which focus on the contextual approach, which are the historical, social and psychological approach. The study relied on the descriptive-analytical approach, by which it analyzes the text of the song using the three methods of literary criticism approach as mentioned before. The study shows that: (1) Palestinian revolutionary folk songs play an important role in constructing the national identity, and (2) the poet Sa’eed al-Muzayyen lived in the period where the Palestinian revolution flared up, especially after the Six-Day War or known as the “al-Naksah”. He himself was influenced and affected by the war which escalated and intensified his spirit of resistance. This infliction is expressed throughout the text of this song. Juxtaposition, this song has also impacted the society as it calls for resistance for the survival of Palestine.